Analysis of the Effect of Data Elements on the Total Factor Productivity of Enterprises in the Digital Economy - Ni, Tianxin (Journal of Global Economy, Business and Finance, 2025)
Total factor productivity is a path choice for achieving high-quality development. As data gradually becomes a new production factor, whether it can become an enabler to improve the total factor productivity of enterprises has become a widely discussed issue in the academic world. Using the data of A-share listed companies from 2001 to 2022, this paper constructs a two-way fixed-effects model to empirically test the impact of data factors on the total factor productivity of enterprises. The results show that data elements have a significant positive impact on enterprise total factor productivity, which remains significant after a series of robustness tests by replacing the explanatory variables, the core explanatory variable measurements, and introducing quasi-natural experiments. It further analyses its transmission mechanism and what different effects will be produced by enterprises in different regions and industries. Finally, combined with the above research, this paper puts forward the corresponding policy recommendations. Increase the cultivation of talents and the introduction of talents; achieve the issue of increasing total factor productivity in the context of high-quality development of the economy by fully leveraging the role of data elements; guide enterprises to make rational use of data elements; and balance the level of development of data elements.